Applying the Most Significant Change (MSC) Method: A case study using the Business Acceleration for Youth Project in Malawi - Mzumara, Grace; Ngige, Chris Mwangi; Nkhambule, Emily; Sheriff, Ramadhan Kadammanja; Slane, David (2024)
This insight note documents the application of the Most Significant Change (MSC) methodology in USAID Malawi's Business Acceleration for Youth project. MSC is a participatory qualitative approach that captures project outcomes through stakeholder storytelling. The project targeted youth-led enterprises (ages 18-35) across agriculture, agroprocessing, tourism, and manufacturing sectors in four Malawian districts.